Influencing factors of health screening among retirees: an extended TPB approach - Xu, Jiayi; Pan, Younghwan; Li, Qiongzhen (Frontiers in Public Health, 2024)
Background Health screenings are promoted worldwide as they help detect and prevent overall health issues. Despite expanding coverage, the participation rate among the retired population has not significantly increased. Given the special role of health screenings in promoting health and healthy aging, understanding the behavioral intentions, and influencing factors of retirees’ voluntary participation in health screenings is crucial. This study aims to explore the participation intentions in health screenings among the Chinese retired population by integrating the Theory of Planned Behavior (TPB) and Self-Efficacy (SE). Methods This study used a cross-sectional design to conduct an online questionnaire among 311 retirees in 2023. The questionnaire, tailored for the Chinese retired population, combines the TPB theory and Self-Efficacy theory, including demographic structure, the basic structure of TPB, and SE. Results A Structural Equation Modeling (SEM) approach was used to identify factors related to health screening behaviors. Of the respondents, 311 completed the survey (88.9% response rate). The most crucial determinant of health examination behavior was behavioral intention, with a correlation score of (1.524, p < 0.001). Significant correlates of behavioral intention included Subjective Norms (SN) and Self-Efficacy (SE), followed by Perceived Behavioral Control (PBC) and Attitude (AT), with correlation scores of (0.401, p < 0.001), (0.339, p < 0.001), (0.082, p < 0.001), and (0.060, p < 0.05), respectively. Conclusion This study provides insights for enhancing the willingness and behavior of retirees to participate in health screenings.